Practicality and Effectiveness of New Technopreneurship Incubator Model in The Digitalization Era - Larisang, Larisang; Sanusi, Sanusi; Bora, M. Ansyar; Hamid, Abdul (Pandawan, 2025)
The development of business incubators within colleges is gaining traction in Indonesia as a strategic approach to fostering business start-up innovation and enhancing entrepreneurial interest among younger generations. It is widely believed that these incubators can serve as effective methods to stimulate business innovation and entrepreneurial endeavors among students, alumni and businessmen. This study aims to evaluate the practicality and effectiveness of a newly designed incubator model, as perceived by experts and tenants. Data were collected through interviews and questionnaires distributed to five entrepreneurship course lecturers and ten entrepreneurial groups. The findings reveal that the practicality of the designed model was assessed using the Total Response Rate (TRR), which resulted in an 89.2% score, placing it in the